Microbial Removal of Petroleum Hydrocarbons from Contaminated Soil under Arsenic Stress - Qu Su; Jiang Yu; Kaiqin Fang; Panyue Dong; Zheyong Li; Wuzhu Zhang; Manxia Liu; Luojing Xiang; Junxiong Cai (Toxics, 2023)
The contamination of soils with petroleum and its derivatives is a longstanding, widespread, and worsening environmental issue. However, efforts to remediate petroleum hydrocarbon-polluted soils often neglect or overlook the interference of heavy metals that often co-contaminate these soils and occur in petroleum itself. Here, we identified Acinetobacter baumannii strain JYZ-03 according to its Gram staining, oxidase reaction, biochemical tests, and FAME and 16S rDNA gene sequence analyses and determined that it has the ability to degrade petroleum hydrocarbons. It was isolated from soil contaminated by both heavy metals and petroleum hydrocarbons. Strain JYZ-03 utilized diesel oil, long-chain n-alkanes, branched alkanes, and polycyclic aromatic hydrocarbons (PAHs) as its sole carbon sources. It degraded 93.29% of the diesel oil burden in 7 days. It also had a high tolerance to heavy metal stress caused by arsenic (As). Its petroleum hydrocarbon degradation efficiency remained constant over the 0–300 mg/L As(V) range. Its optimal growth conditions were pH 7.0 and 25–30 °C, respectively, and its growth was not inhibited even by 3.0% (w/v) NaCl. Strain JYZ-03 effectively bioremediates petroleum hydrocarbon-contaminated soil in the presence of As stress. Therefore, strain JYZ-03 may be of high value in petroleum- and heavy-metal-contaminated site bioremediation.